Biomimetic Boron Nitride Nanoparticles for Targeted Drug Delivery and Enhanced Antitumor Activity - Hui Li; Wei Qiao; Yizhe Shen; Huashan Xu; Yuan Fan; Yuxiang Liu; Yadi Lan; Yan Gong; Fuxue Chen; Shini Feng (MDPI AG, 2023)
Boron nitride nanomaterials are being increasingly recognized as vehicles for cancer drug delivery that increase drug loading and control drug release because of their excellent physicochemical properties and biocompatibility. However, these nanoparticles are often cleared rapidly by the immune system and have poor tumor targeting effects. As a result, biomimetic nanotechnology has emerged to address these challenges in recent times. Cell-derived biomimetic carriers have the characteristics of good biocompatibility, long circulation time, and strong targeting ability. Here, we report a biomimetic nanoplatform (CM@BN/DOX) prepared by encapsulating boron nitride nanoparticles (BN) and doxorubicin (DOX) together using cancer cell membrane (CCM) for targeted drug delivery and tumor therapy. The CM@BN/DOX nanoparticles (NPs) were able to target cancer cells of the same type on its own initiative through homologous targeting of cancer cell membranes. This led to a remarkable increase in cellular uptake. In vitro simulation of an acidic tumor microenvironment could effectively promote drug release from CM@BN/DOX. Furthermore, the CM@BN/DOX complex exhibited an excellent inhibitory effect against homotypic cancer cells. These findings suggest that CM@BN/DOX are promising in targeted drug delivery and potentially personalized therapy against their homologous tumor.